Adapting Porter’s generic strategies to vocational education: a conceptual framework for enhancing SMK institutional competitiveness - Erlita Aryanti Widiastuti; Bernadetha Nadeak; Hotmaulina Sihotang (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This article examines how Porter’s generic strategies can be adapted to strengthen the competitiveness of Indonesian Vocational High Schools (Sekolah Menengah Kejuruan/SMKs). The study aims to analyze the application of cost leadership, differentiation, and focus strategies in designing institutional strategies that address industry demands. A qualitative conceptual literature review was conducted using document analysis, thematic classification, and conceptual synthesis of studies on strategic management, vocational education, school competitiveness, and school–industry partnerships. The findings indicate that cost leadership should be interpreted as value-based efficiency that improves resource productivity without compromising learning quality. Differentiation should be achieved through industry-relevant curricula, project-based learning, professional certification, and credible institutional branding, supported by adequate teacher competence and facilities. The focus strategy is most effective when SMKs develop regional specialization based on labor-market analysis, competency niches, strategic industry partnerships, and outcome-based evaluation. The study proposes an integrated strategic model comprising strategic diagnosis, strategy configuration, implementation governance, and performance evaluation. This model contributes to strategic educational management by reframing Porter’s business-oriented framework as a practical approach to strengthening SMK institutional competitiveness.